2009
DOI: 10.1007/s11244-009-9346-6
|View full text |Cite
|
Sign up to set email alerts
|

N2O Abatement Over γ-Al2O3 Supported Catalysts: Effect of Reducing Agent and Active Phase Nature

Abstract: A series of metal catalysts (Pd, Rh, Ru, Cu, Fe, In and Ni) supported on c-Al 2 O 3 carrier, were evaluated during N 2 O catalytic conversion to N 2 in the absence and presence of excess oxygen and reducing agents (CH 4 or C 3 H 8 ). Among all catalysts tested, Pd-, Ru-and Rh-based samples exhibited the best catalytic performance, in all reaction conditions examined. The reaction was inhibited by O 2 , in particular at lower temperatures, while its effect was essentially negligible at higher ones. In the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 25 publications
(47 reference statements)
0
14
0
Order By: Relevance
“…Regarding the role of hydrocarbons it has been established in our previous study concerning the N 2 O decomposition/reduction over different supported catalysts, that even in the presence of hydrocarbons the N 2 O decomposition (step 3b) is the major step for N 2 O abatement [30]. However, the adsorption strength of hydrocarbon is expected to significantly affect the population of active sites for N 2 O decomposition; the higher the adsorption strength of hydrocarbon with catalyst surface, the fewer the active sites for N 2 O activation.…”
Section: Discussionmentioning
confidence: 97%
“…Regarding the role of hydrocarbons it has been established in our previous study concerning the N 2 O decomposition/reduction over different supported catalysts, that even in the presence of hydrocarbons the N 2 O decomposition (step 3b) is the major step for N 2 O abatement [30]. However, the adsorption strength of hydrocarbon is expected to significantly affect the population of active sites for N 2 O decomposition; the higher the adsorption strength of hydrocarbon with catalyst surface, the fewer the active sites for N 2 O activation.…”
Section: Discussionmentioning
confidence: 97%
“…Regarding the mechanism of N 2 O reduction by hydrocarbons it is generally accepted that N 2 O abatement over noble metals proceeds mainly via N 2 O adsorption and its subsequent scission to N 2 (g) and O(ad). To this end, it has been established in a previous study concerning the N 2 O decomposition/ reduction over supported catalysts that even in the presence of hydrocarbons N 2 O decomposition is the main step for N 2 O elimination [10]. In other words, the role of the hydrocarbon is limited to determining the available sites for N 2 O adsorption via its adsorption affinity and its ability to scavenge the catalyst's surface by strongly adsorbed O(ad).…”
Section: Mode Of Action Of K-promoter During N 2 O Reductionmentioning
confidence: 99%
“…In our previous study concerning the effect of metal nature (M: Pd, Rh, Ru, Cu, Fe, In, Ni) and reducing agents on N 2 O decomposition over several M/Al 2 O 3 supported catalysts, it was found that Pd/Al 2 O 3 catalysts are among the most active ones for N 2 O abatement [10]. In the present work, motivated by the enhanced de-N 2 O activity of Pd/Al 2 O 3 catalysts as well as the significant modifications that can be induced by electropositive promoters on Pd surface chemistry [11], we focus on the effect of potassium (K) promoter on N 2 O reduction by hydrocarbons over Pd/Al 2 O 3 catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…There are many catalysts that can be used for N2O decomposition including perovskites [11][12][13][14][15], ceriabased catalysts [16][17][18], spinels [19][20][21] and supported metal catalysts [22][23][24][25][26]. This work focuses on palladium/alumina (Pd-Al2O3) catalysts as these have not been extensively studied to date [27][28][29][30][31] and similar catalytic systems have been demonstrated to exhibit high activity and stability in similar applications [32][33][34][35][36][37]. Pekridis et al reported a T100 (i.e.…”
Section: N2o  N+ O2mentioning
confidence: 99%